PRODUCTION AND PERFORMANCE APPRAISAL OF BIODIESEL DERIVED FROM USED COOKING OIL ON COMPRESSION IGNITION ENGINE - Suleiman, Ismail A.; Abubakar, Shitu; Kaisan, Muhammad Usman; Magaji, Suleiman; Abubakar, Aminu Sahabi; Shitu, Sabiu; Ajunwa, Isaaac; Ibrahim, Ibrahim Umar; Umaru, Samaila (FUDMA JOURNAL OF SCIENCES, 2020)
The present study is concerned with the production of biodiesel produced from used cooking groundnut oils using alkali trans-esterification reaction. Gas chromatography-mass spectrometry (GC-MS) and Fourier-transform infrared spectroscopy (FTIR) analyses were carried out on the biodiesel produced and the presence of methyl esters and their various functional groups were detected. The Physico-chemical properties of the biodiesels produced were also carried out and most of the properties conformed to ASTM standards. The biodiesel samples were tested in a 165F- Horizontal Single Cylinder Direct Injection Diesel Engine at Bayero University Kano (BUK), Kano State, Nigeria, investigating parameters such as: Brake power, Specific fuel consumption and Brake mean effective pressure. The exhaust gas was analysed in an NHA-506EN automotive gas analyzer, from Nigerian Institute of Transport Technology, Zaria, Kaduna State, where parameters such as hydrocarbon (HC), nitrogen oxide (NOx), carbon monoxide (CO) and carbon (IV) oxide (CO2) were all analyzed. The results showed that the oil from frying yam yielded 87.5% while that from frying fish yielded 94% and the biodiesels produced conformed to most of the Physico-chemical properties according to the ASTM standards. Also, the engine results demonstrated that there was improved brake power and mean effective pressure but the specific fuel consumptions were higher than that of the control sample. Lastly, the exhaust gas emissions results showed that there were significant reductions in carbon monoxide (CO), nitrogen oxide (NOx), carbon IV oxide (CO2) and hydrocarbon emissions showing us that biodiesel is more eco-friendly.